Management of Infantile Hemangioma in the Community (Canadian Dermatology Today, 2025)
I practice as a general medical dermatologist in Northern British Columbia. During my first year of practice, I saw several infants requiring treatment for an infantile hemangioma, which required me to become familiar with topical and systemic therapies. The objective of this article is to provide an overview of the management of uncomplicated infantile hemangiomas in community settings, helping dermatologists become confident in prescribing first-line topical and systemic therapies.